Assessment of nutritional status and health challenges among female garment workers: a cross-sectional study - Newaz, Taslima; Dutta, Arup; Rahman, M. Shafiur; Hossain, Moynal; Hoque, M. Ahasanul; Purba, Srobonti Dutta (International Journal Of Community Medicine And Public Health, 2024)
Background: The economic status of women is now accepted as an indicator of a society’s development in Bangladesh. Women workers like the majority in the informal sector have been exposed to rigorous work, discipline, fixed working hours, specific production norms etc. The aim of the study was to perform cross-sectional study was conducted to assess nutritional status of female garment workers in Chattogram, Bangladesh. Methods: The study was conducted with the help of a semi-structured questionnaire to collect data from the respondents by face-to-face interview. Informed written consent was obtained from the respondents. A checklist containing height and weight (measured using measuring tape and digital weight machine respectively) of the respondents included in the questionnaire. Results: According to the study, gastrointestinal problem was reported by 49.7% and the rest reported problem were respiratory problem (35.3%), skin problem (27.3%), urinary problem (18%), eye problem (15%). Age, marital status, number of children, family member, monthly income, job section, working hours and overtime were significantly associated with various types of health problem. Respondents were categorized into underweight (≤18.5 kg/m2), normal (18.6-24.9 kg/m2) and overweight and above (≥25.0 kg/m2) using BMI. Prevalence of underweight, normal and overweight and above were 3.3%, 61.3% and 35.3% respectively. Conclusions: Female worker’s age, marital status, number of children, monthly income, job duration, job section and overtime showed significant association with their nutritional status (BMI). Findings of this study may play an important role to develop a policy and in commercial sector of our country to reduce health problem of the female garment workers for better productive and healthy lifestyle.